Liquidity management in liberalising economies : some experiences from the Caribbean - Clarke, Laurence C.; Leon, H. L. ([St. Augustine, Republic of Trinidad and Tobago] : Caribbean Centre for Monetary Studies, 1996)
The publication is the outcome of a wide ranging reconsideration of an important facet of monetary policy, namely liquidity management.
Includes index.
gp. 24/01/2019
Loans
Keywords: Monetary policy; Liquidity (Economics); Balance of payments; Banks and banking, Central